Artificial Intelligence Based Marketing Strategies During the Digital Era - Wentri Merdiani (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The aim of this study is to explain the roles of the artificial intelligence on the marketing strategies. The method used is systematic secondary data search and meta analysis. The findings of the research are as follows: First, The pervasive integration of ai across marketing functions. Second, The rise of hyper-personalization powered by AI. Third, AI-driven automation for enhanced efficiency and productivity. Fourth, The Evolution of AI in content creation and curation. Fifth, Navigating the ethical considerations and future of AI in marketing. Sixth, The most impactful AI applications for digital advertisers at present. Seventh, How small businesses leverage AI in their marketing efforts. Eighth, some common misconceptions about AI in marketing. Ninth, Marketers can upskill to work effectively with AI tools. Tenth, The key metrics for measuring the success of AI-powered marketing initiatives. Eleventh, How to Create an AI Digital Marketing Strategy in 7 Steps. Twelveth, Artificial Intelligence Technologies for Marketing.